Copper-Catalyzed Synthesis of S-Aryl Dithiocarbamates from Tetraalkylthiuram Disulfides and Aryl Iodides in Water - Wu, Xiang-mei; Yan, Guo-bing (Synlett, 2019)
An efficient approach for the copper-catalyzed synthesis of aryl dithiocarbamates from aryl iodides and tetraalkylthiuram disulfides in water is described. Without additional ligand and organic solvent, the coupling reaction could provide a series of S-aryl dithiocarbamates in moderate to good yields.
Keywords: copper; aryl dithiocarbamate; aryl iodide; tetraalkylthiuram disulfide; water